Solariella quadricincta Quinn, 1992 and S. staminea Quinn, 1992 are synonyms of S. carvalhoi Lopes & Cardoso, 1958 from the SW Atlantic (Gastropoda: Solariellidae) - Cavallari, Daniel C.; Salvador, Rodrigo B.; Simone, Luiz R. L. (Zootaxa, 2016)
Solariellidae is a diverse family of small (5–20 mm) marine snails of worldwide distribution. They usually live on fine sediment to unconsolidated substrates in deep-waters of extra-tropical to tropical latitudes (Hickman 1998; Williams et al. 2013). Initially described as a subfamily of Trochidae, it has been recently raised to family level (Bouchet et al. 2005; Williams et al. 2008). The evolutionary relationships among solariellids have been extensively investigated in the light of morphological and molecular data, but the family still lacks a comprehensive taxonomic revision that reflects recent discoveries (Williams et al. 2010, 2013). The family’s fossil record possibly dates back to the Campanian of Torallola, Spain (Kiel & Bandel 2001; Williams et al. 2013).